Hakikat Hereditas dan Lingkungan Perspektif Pendidikan Islam dalam Pembelajaran Anak Usia Dini - adihaironi adi; Faiz Naufal (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
Every human being is born with their own potential and this next journey will be influenced by the environment in which the child or individual lives. It can be concluded that the ability of a person will develop well if he has good character and good environment or vice versa. This is clearly influenced by two factors, heredity and environment. Then does it stop there? There is still one more factor that can change the experience of the two factors above, namely reason. So here the role of education is very important, where human potential, especially those who can be said to be pure, can develop optimally. That is by examining the two factors above in the view of Islamic education. So that later the concept of education to achieve the goal of Islamic education can be achieved maximally. Education is an urgent matter for the development of abilities that exist in every human being. We know that every person born has their own potential